Analysis of Share Investment Decision Making Using The Capital Asset Pricing Model (CAPM) Method in Companies Registered In IDX30 2018-2021 Period - Sari, Meilinda Lutfita; Atmadjaja, Yovita Vivianty Indriadewi; Ferawati, Indah Wahyu (Lembaga Riset dan Inovasi Al-Matani, 2022)
ABSTRACT In investing, the accuracy of potential investors in digging and processing information will be used as a decision making tool for investing which will determine how much risk and profit will be obtained in the future. The research objective is to analyze risk and stock returns and classify efficient and inefficient stocks by applying the Capital Asset Pricing Model (CAPM) method to stocks listed in IDX30 for the 2018-2021 period. This research uses descriptive research with a quantitative approach using secondary data in the form of monthly closing prices, monthly Composite Stock Price Index (IHSG) and monthly SBI interest rates (BI Rate). The population in this study are companies listed on the IDX30 on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The number of samples in this study were 19 shares. The sampling technique in this study used purposive sampling. The data collection method in this study uses the documentation method. The data analysis technique used is the Capital Asset Pricing Model (CAPM) method. The results showed that of the 19 company stocks sampled, there were twelve (12) stocks that were classified as efficient or undervalued stocks because the individual return (Ri) was greater than the expected rate of return [E(Ri)], these stocks were ADRO, ANTM, BBCA, BBNI, BBRI, BBTN, BMRI, ICBP, KLBF, PGAS, SMGR and TLKM, the recommended decision for investors is to buy shares and there are seven (7) shares which are classified as inefficient or overvalued shares due to individual returns. (Ri) is smaller than the expected rate of return [E(Ri)], these stocks are ASII, GGRM, HMSP, INDF, INTP, UNTR, and UNVR, the recommended decision to investors is to sell shares.